2015
DOI: 10.4102/sajbm.v46i3.100
|View full text |Cite
|
Sign up to set email alerts
|

Share repurchase and dividend payout behaviour: The South African experience

Abstract: Share repurchases, rather than dividend payments, are increasingly becoming the globally favoured payout method. This has prompted a renewed interest in the field, and raises questions about the actual motivation for share repurchases and whether companies are now repurchasing shares in preference to investing in future growth. This study set out to ascertain whether South African company payout behaviour mirrors global company behaviour. Comprehensive data on share repurchases are, however, not compiled by So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(70 citation statements)
references
References 0 publications
3
67
0
Order By: Relevance
“…When comparing the three specific share repurchase types in South Africa (namely the pro rata offer, and the two private offers), it was found that, for reporting periods from 1999 to 2009, the repurchase by the holding company of the shares held by subsidiaries was the favoured specific share repurchase type (representing about 55% of total specific repurchase value), while pro rata offers and other specific offers represented about 32% and 13% of the total specific repurchase value, respectively (Wesson et al, 2015). The fact that subsidiaries are allowed to repurchase shares in their holding company has therefore affected share repurchase behaviour in the South African regulatory environment: the open market share repurchase type is not the favoured share repurchase type, and the repurchase by the holding company of shares held by subsidiaries represents about 31% of total share repurchase value -hence resulting in specific repurchases being the favoured share repurchase method (Wesson et al, 2015).…”
Section: Private Offersmentioning
confidence: 99%
See 4 more Smart Citations
“…When comparing the three specific share repurchase types in South Africa (namely the pro rata offer, and the two private offers), it was found that, for reporting periods from 1999 to 2009, the repurchase by the holding company of the shares held by subsidiaries was the favoured specific share repurchase type (representing about 55% of total specific repurchase value), while pro rata offers and other specific offers represented about 32% and 13% of the total specific repurchase value, respectively (Wesson et al, 2015). The fact that subsidiaries are allowed to repurchase shares in their holding company has therefore affected share repurchase behaviour in the South African regulatory environment: the open market share repurchase type is not the favoured share repurchase type, and the repurchase by the holding company of shares held by subsidiaries represents about 31% of total share repurchase value -hence resulting in specific repurchases being the favoured share repurchase method (Wesson et al, 2015).…”
Section: Private Offersmentioning
confidence: 99%
“…The fact that subsidiaries are allowed to repurchase shares in their holding company has therefore affected share repurchase behaviour in the South African regulatory environment: the open market share repurchase type is not the favoured share repurchase type, and the repurchase by the holding company of shares held by subsidiaries represents about 31% of total share repurchase value -hence resulting in specific repurchases being the favoured share repurchase method (Wesson et al, 2015).…”
Section: Private Offersmentioning
confidence: 99%
See 3 more Smart Citations